Pemanfaatan Media Interaktif dalam Strategi Pembelajaran PAI untuk Meningkatkan Motivasi Belajar Peserta Didik - Dimas Purnomo; Muhammad Afif Marta; Gusmaneli Gusmaneli (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study explores the use of interactive media in Islamic Religious Education (PAI) teaching strategies to enhance students' learning motivation. The research employs a literature review method by analyzing relevant sources. The findings indicate that interactive media, such as animated videos, digital applications, simulations, and Augmented Reality (AR) and Virtual Reality (VR) technologies, can improve student engagement and comprehension in PAI learning. These media make the learning process more engaging, enhance material retention, and encourage independent learning. However, its implementation still faces challenges, including limited technological infrastructure and teachers' lack of digital media management skills. Therefore, appropriate strategies are needed to optimize the use of interactive media in PAI education to improve the effectiveness of religious learning in the digital era.